Caracterização técnica e econômica de arranjos produtivos de Café na Microrregião do Caparaó: ES - Abdallah, Fabrizio Raggi (2010)
In Brazil Espírito Santo state is the first producer of Conilon coffee and the third of Arábica coffee. The Caparaó Microregion, located at southwest of the state, nests ten municipal districts, where 86.7% of them produce Arábica coffee. In order to amel